River engineering works and lamprey ammocoetes; impacts, recovery, mitigation. (22nd July 2015) - King, James J.; Wightman, Glen D.; Hanna, Grainne; Gilligan, Nathy
Abstract: Channel form and biotic features create a network of niches that facilitate sediment deposition, creating habitat for lamprey larvae or ammocoetes. Flood conveyance management and channel maintenance can lead to a general loss of instream features that permit biotic diversity and sediment deposition. Studies presented here identified the potential for loss of both ammocoete habitat and populations during channel maintenance, in the absence of mitigation measures. Recovery of population structure and density of ammocoetes commenced within 12 months and took 3 years to reach preimpact levels in one study. In another, where mitigations were implemented, no impact was evident 12 months after channel maintenance. In view of the conflict between conveyance for flood management and conservation of designated Habitats Directive species (lamprey), there is a clear need for practical ammocoete mitigation measures to be developed and implemented in river engineering works.